Chemical composition, antioxidant, antimicrobial and antiviral activities of the leaf extracts of Syzygium myrtifolium - AHMAD MUSTAFFA ALBAKRI; LIM YI HUI; CHAN YIK SIN; HSU CHUN-YUAN; WU TZONG-YUAN; SIT NAM WENG (Acta Pharmaceutica)
This study was conducted to evaluate the chemical composition and biological activities of the leaf extracts of Syzygium myrtifolium Walp. (Myrtaceae). The results indicate that the leaf extracts of S. myrtifolium contain various classes of phytochemicals (alkaloids, anthraquinones, flavonoids, phenolics, saponins, tannins and triterpenoids) and possess antioxidant, antibacterial, antifungal and antiviral activities. Ethyl acetate, ethanol, methanol, and water extracts exhibited significantly higher (p < 0.05) oxygen radical absorbance capacity and ferric-reducing antioxidant power than the hexane and chloroform extracts. However, all extracts exhibited stronger inhibitory activity against four tested species of yeasts (minimal inhibitory concentration: 0.02–0.31 mg mL–1) than against six tested species of bacteria (minimal inhibitory concentration: 0.16–1.25 mg mL–1). The ethanolic extract offered the highest protection of Vero cells (viability > 70 %) from the cytopathic effect caused by the Chikungunya virus while the ethyl acetate extract showed significant replication inhibitory activity against the virus (p < 0.001) using the replicon-enhanced green fluorescent protein reporter system.